Delayed Gadolinium‐Enhanced Magnetic Resonance Imaging of Medial Tibiofemoral Cartilage and Its Relationship With Meniscal Pathology: A Longitudinal Study Using 3.0T Magnetic Resonance Imaging. Issue 6 (June 2014) - Crema, Michel D.; Hunter, David J.; Burstein, Deborah; Roemer, Frank W.; Li, Ling; Krishnan, Nitya; Marra, Monica D.; Hellio Le‐Graverand, Marie‐Pierre; Guermazi, Ali
<x xml:space="preserve">Abstract</x> Objective To evaluate the relationship between medial meniscal pathology and cartilage matrix status using delayed gadolinium‐enhanced magnetic resonance imaging of cartilage (dGEMRIC) in medial tibiofemoral cartilage in a sample of middle‐aged women. Methods A total of 148 women ages ≥40 years were included, and 3.0T MRI of the knee was performed at baseline and at 1 year. T2‐weighted, fat‐suppressed and 3‐dimensional inversion recovery–prepared spoiled gradient‐recalled echo sequences were acquired 90 minutes after gadolinium injection. Baseline medial meniscal pathology was scored on a scale of 0–3, where 0 = normal, 1 = intrasubstance meniscal signal change, 2 = single tears, and 3 = complex tears/maceration. The central medial femur, the medial tibial plateau, and the posterior medial femur were subjected to dGEMRIC at baseline and at 1 year. Analysis of covariance was used to examine whether baseline and 1‐year dGEMRIC indices in the same regions were related to the severity of meniscal damage at baseline, using normal medial menisci (grade 0) as the reference. Results Medial compartments with grade 3 lesions showed significantly lower dGEMRIC indices (less proteoglycan content) at the central medial femur region compared with compartments with normal menisci. Mean ± SEM differences in dGEMRIC indices between grade 3 and grade 0 menisci at the central medial femur were −119.1 ± 34.2 msec at baseline (P = 0.03) and −120.3 ± 35.2 msec at followup (P = 0.04). Conclusion High‐grade damage of the medial meniscus showed significant associations with lower dGEMRIC indices. The dGEMRIC technique may be a useful tool in detecting early degenerative changes of cartilage when meniscal function is lost.